2006
DOI: 10.1038/sj.onc.1209541
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the carcinoembryonic antigen-related cell adhesion molecule 1 (Ceacam1) gene contributes to colon tumor progression in a murine model of carcinogenesis

Abstract: Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) is a glycoprotein that is part of the carcinoembryonic antigen and the immunoglobulin superfamilies. We have shown that it functions as a tumor suppressor and that this function depends upon the presence of the longer CEACAM1 cytoplasmic domain. In this report, we describe the generation of a Ceacam1À/À mouse. The Ceacam1À/À colon exhibits increased in vivo proliferation relative to the wild-type counterpart with a corresponding decreased expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 55 publications
6
96
0
1
Order By: Relevance
“…The results showed that CEACAM1 significantly enhanced p21 but not p27 expression and conversely downregulation of CEA-CAM1 decreased p21 but not p27 expression. These data are in partial agreement with a recent report where CEACAM1 depletion was shown to be associated with diminished p21 and p27 in mouse colonic epithelium (Leung et al, 2006).…”
Section: Ceacam1 In Thyroid Cancer W Liu Et Alsupporting
confidence: 93%
“…The results showed that CEACAM1 significantly enhanced p21 but not p27 expression and conversely downregulation of CEA-CAM1 decreased p21 but not p27 expression. These data are in partial agreement with a recent report where CEACAM1 depletion was shown to be associated with diminished p21 and p27 in mouse colonic epithelium (Leung et al, 2006).…”
Section: Ceacam1 In Thyroid Cancer W Liu Et Alsupporting
confidence: 93%
“…18 Wild-type and ceacam1 ϩ/Ϫ mice were age-and sex-matched C57BL/6. These mice were housed in the Burnet Institute …”
Section: Micementioning
confidence: 99%
“…18 Antirabbit fluorescein isothiocyanate (FITC) was purchased from Dako (Botany, Australia). Anti-mouse GPVI, 19 anti-mouse GPIb␣/IX/V complex, 20 anti-mouse integrin ␣2␤1, 21 anti-mouse CD9, 22 and anti-mouse GPVI (JAQ1) 23 were purchased or obtained from Emfret Analytics (Wü rzburg, Germany).…”
Section: Antibodiesmentioning
confidence: 99%
“…In support of the role of CEACAM1-L in inhibition of tumor growth, we have recently shown that Ceacam1 À/À normal colon exhibits increased proliferation and decreased apoptosis. Upon azoxymethane carcinogenic induction, a greater number of colon tumors form in CEACAM1-deficient mice relative to littermate controls (Leung et al, 2006). However, as both Ceacam1 and Apc loss of function represent early events in intestinal cancer development, we questioned whether deletion of the Ceacam1 gene influenced intestinal tumor progression driven by the Apc loss of function and whether both genes impacted on the same signaling pathways.…”
Section: Introductionmentioning
confidence: 99%